2015
DOI: 10.1007/s00439-015-1552-7
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in CST3 exerts a recessive effect on susceptibility to age-related macular degeneration resembling its association with Alzheimer’s disease

Abstract: Age-related macular degeneration (AMD) and Alzheimer’s disease (AD) are degenerative, multifactorial diseases involving age-related accumulation of extracellular deposits linked to dysregulation of protein homeostasis. Here, we strengthen the evidence that an nsSNP (p.Ala25Thr) in the cysteine proteinase inhibitor cystatin C gene CST3, previously confirmed by meta-analysis to be associated with AD, is associated with exudative AMD. To our knowledge, this is the first report highlighting a genetic variant that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…In addition, we report a common polymorphism in CST3 (p.A25T), whose homozygous carrier frequency was significantly higher compared to HEX controls (4.16% and 1.63%, respectively). Interestingly, this polymorphism has been already associated to macular degeneration and LOAD 40 . The presence of one or two minor alleles increases LOAD risk and lowered the age at onset, in a fashion described both independent and dependent from APOE ε4 allele 39,53 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, we report a common polymorphism in CST3 (p.A25T), whose homozygous carrier frequency was significantly higher compared to HEX controls (4.16% and 1.63%, respectively). Interestingly, this polymorphism has been already associated to macular degeneration and LOAD 40 . The presence of one or two minor alleles increases LOAD risk and lowered the age at onset, in a fashion described both independent and dependent from APOE ε4 allele 39,53 .…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, homozygosity for CST3 p.A25T has been significantly associated with AD 39 and other neurodegenerative conditions such as macular degeneration 40 . In our cohort, we report 4/96 [4.16%] patients homozygous for the minor allele A, a carrier frequency which was 2.55 times higher when compared with HEX controls (6/368 [1.63%]).…”
Section: App-aβ Metabolism Genesmentioning
confidence: 99%
“…In addition, the authors revealed that reduced levels of CST3 may impair the neuronal ability to prevent neurodegeneration in AD (105). Recently, Butler et al (106) found that a missense variant in CST3 rs1064039 was associated with age-associated macular degeneration and AD.…”
Section: Cystatin C (Cst3)mentioning
confidence: 99%
“…year later, CST3, previously confirmed by meta-analysis to be associated with AD, has been found to be associated also with exudative AMD (40). Finally, a study by Hoffman and colleagues tried to search for a possible correlation with AMD progression, defined by using drusen number and total area, and a set of selected genetic loci, but they failed to find any significant correlation (41).…”
Section: Risk Factors Protective Agents and Associated Conditionsmentioning
confidence: 99%